Constant current-fuzzy logic algorithm for lithium-ion battery charging - Muhammad Nizam; Hari Maghfiroh; Azis Ubaidilah; Inayati Inayati; Feri Adriyanto (Institute of Advanced Engineering and Science, 2022)
The lithium-ion (Li-ion) battery has a high demand because of its long cycle, reliability, high energy density, low toxic, low self-discharge rate, high power density, and high efficiency. However, lithium-ion batteries have sensitivity to over-charge, temperature, and charge discharge currents. The conventional battery charging system takes a very long time to charge which makes the battery temperature high. Therefore, a charger system that can maximize charging capacity, shorten charging time, and extend battery life is needed. In this study, a battery charging system was developed using the constant current–fuzzy (CC-fuzzy) control method. The aim is to get faster charging time and maintain battery life by limiting the battery charging temperature. The proposed charger system is dual mode which can be operated in both buck and boost mode. The experimental result shows that the proposed method is superior compared to the constant current constant voltage (CCCV) method in charging time. The CC-fuzzy method charging time is faster compared to the CCCV method by 25% and 12.5% in buck and boost modes, respectively. Whereas from the battery temperature, in buck mode, the proposed method has a lower temperature by 0.5 ⁰C and in the boost mode, each method has the same temperature.